DEMOGRAPHY AND IT’S INFLUENCE IN THE URBAN DEVELOPMENT OF A COUNTRY - Lubonja, Otjela; Pipa, Donila (European Scientific Journal, ESJ, 2014)
Urbanization brings a sustainable development as it closely relates to demography, the movement of population. After 1990, in contrast to the communist regime era a shift from the planned population movements, to congestion mainly toward Tirana and other coastal areas has been noticed. The aim of this paper is to analyze the impact that the population movement has had into our country’s urban development. Urbanization is considered to be a major component for the economic growth of a country, especially in coastal areas, in which it is more incentive for sustainable development.The urbanization has passed through several stages: pre-industrial, industrial and postindustrial one. It is seen as a means to improve civilization, while bringing more progress and development. So we may ask: Was it worth a movement of population without a plan in Albania and should we put nowadays a planning strategy for the urbanization and demography?